PATTERN OF NOSOCOMIAL INFECTION AMONG PATIENTS ADMITTED IN MEDICAL AND SURGICAL WARDS OF A SECONDARY CARE HOSPITAL IN NORTH INDIA-AN EPIDEMIOLOGICAL EVALUATION - Saleem, Mohd; Vaish, Arvind Kumar; Idris, Mohd Zafar; Sonkar, Abhinav Arun; Agarwal, Jyotsna; Singh, Mastan; Singh, Shivendra Kumar; Srivastava, Vinod Kumar (Indian Journal of Community Health, 2012)
Objective: Nosocomial infections occur worldwide and affect both developed and resource-poor countries. Infections acquired in health care settings are amongst the major causes of death and increased morbidity among hospitalized patients. In this study, we aimed to determine the epidemiological status of nosocomial infections in the Medical and Surgical Wards of a secondary care hospital. Study design: Cross sectional hospital based study. Study site: Department of Medicine, General Surgery and Orthopedic Surgery, Dr. Shyama Prasad Mukherji (Civil Hospital) Lucknow. Patients: The patients admitted in the Department of Medicine, General Surgery and Orthopedic Surgery were included in this study. Results: The present study has been carried out on 176 patients (Medical ward=82, Surgical ward=94). This study was conducted between January 2011 to December, 2011. All the 176 patients were clinically examined. Among them, fever was found in 140 patients. A total of 63 blood, 27 pus/discharge, 25 sputum and 85 urine specimen were collected from the patients who developed fever after 48 hours of admission. The overall proportion of nosocomial infection was 26.1% (Medical ward-28%; Surgical ward-24.5). The proportion of nosocomial infection was higher among females (33.3%) than males (21.8%). Older patients were more affected than younger (<35 years=20%, >=35 years=29.3%). Conclusions: Nosocomial infections are common in hospitalized patients in the medical and surgical setting. More studies are needed to be carried out in Indian population to plan long term strategies for prevention and management of nosocomial infections.